INTERNALISASI NILAI-NILAI QUR’ANI DALAM KEPRIBADIAN SANTRI DI PONDOK PESANTREN AL ITTIFAQIAH INDRALAYA - Ahmad Abdul Qiso (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2020)
Forming a good and superior personality (muthmainnah) in the midst of inconsistencies in values and the spread of immoral behavior today is a must if you want to give birth to individuals who can compete and compete in the midst of current scientific and technological advancements, and participate active share in the development and development of the state, religion, and nation without failing the values of faith and morality. The solution that the author offers to give birth to good and superior individuals is the internalization of the values of the Qur'an. Departing from this reality, this research will answer the following three problem formulations: (1) What are the programs to internalize the values of the Qur'an in the Al Ittifaqiah pound? (2) What is the personality of the santri ?; and (3) What program is most effective in influencing the personality of students? By using a qualitative method and a phenomenalogical and psychological approach located at Al Ittifaqiah Islamic Boarding School in Indralaya, South Sumatra, the authors conclude: (1) There are 11 programs to internalize Qur'anic values in the Al Ittifaqiah boarding school; (2) In the aspect of hard skills, the students who memorize the Qur'an have a better and superior personality, while in the aspect of soft skills, the students who do not memorize the Qur'an are better and superior; and (3) The most effective program in the process of internalizing Qur'anic values is the tahfidzul Qur'an program.